A STUDY OF THE INFLUENCE OF THE COMPOSITION OF FINE VEGETABLE AND FRUIT POWDERS ON THE QUALITY OF LONG BISCUITS - Svetlana Yakovlevna Koryachkina; Ekaterina Nikolaevna Kholodova; Vladimir Petrovich Koryachkin (Современная наука и инновации, 2022)
It was set up that the use of fine fruit and vegetable powders in the technology of long biscuits leads to improved rheological characteristics of a protracted test, organoleptic and physico-chemical parameters of finished products. The optimal dosage of the compositions of vegetable and fruit powders in the formulation of long biscuits was determined.